Application of ecohydraulic bank protection model to improve river bank stability and biotic community in Surabaya River - Daru Setyo Rini; Endang Arisoesilaningsih; Donny Harisuseno; S Soemarno (Brawijaya University, 2017)
Ecohydraulic river bank protection design was developed as ECO-RIPRAP model and has been applied along 100 meter length to restore accelerated erosion sites in Surabaya River at Wringinanom and Klubuk. The model combined re-profiled and re-vegetated bank with rock toe reinforcement and addition of log groynes at 10 meter length interval. Various native plant species were planted on bank slopes, including water plants Ipomoea aquatica and Pistia stratiotes, grasses and shrubs Ipomoea carnea, Pluchea indica, Saccharum spontaneum, Arundo donax, and native tree species Ficus glomerata, Bambusa arundinacea, Dendrocalamus asper, Bambusa vulgaris, Ficus benjamina, Dillenia indica, Psidium guajava, Arthocarpus camansi, Arthocarpus elasticus, Hibiscus mutabilis, Nauclea sp., Inocarpus edulis, and Syzygium polyanthum. The river bank morphology after ECO-RIPRAP application showed alteration from erosion to sedimentation due to rock toe enforcement, log groynes protection, and increase of plant cover on littoral banks that decreased near bank velocity. The macro-invertebrate community shown increase of taxa richness, EPT richness, %EPT and %Atyidae, but decrease of %Chironomidae at restored sites. The fish community shown increase of taxa richness, increase of abundance by 54.2%, increase of Pangasius micronemus abundance by 25.6%, and increase of Hemibragus nemurus abundance by 6.3 % at restored reach. Rare fish species thrive back at restored area, namely Oxyeleotris marmorata, Mastacembelus unicolor and Hampala macrolepidota.